Multi-criteria social sustainability assessment of highland maize monoculture in Northern Thailand using the SAFA tool - Leknoi, Unruan; Rosset, Peter [UNESP]; Likitlersuang, Suched (Elsevier, 2023)
The Sustainability Assessment of Food and Agriculture System (SAFA) is a multi-criteria sustainability assessment tool developed by the Food and Agriculture Organization in 2014. This study aims to contribute to the debate on multi-criteria sustainability assessments by applying the SAFA to a test case of an agricultural supply chain, including production, processing, distribution, and marketing. The study case of the maize monoculture value chain in the Mae Chaem District of Chiang Mai Province was selected as a typical highland maize monoculture in northern Thailand. The study area is the site of a rapidly expanding peasant farmer boom of maize production and global livestock feed industry. This qualitative research employs in-depth interviews and questionnaires of all participants along the value chain of the study area. Multiple social sustainability dimensions including decent livelihood, fair trading practices, labor rights, equity, human safety and health, and cultural diversity were assessed using the SAFA tool. The analysis results were moderately favorable in terms of social sustainability, which to a notable extent contrasts with sustainability issues surrounding maize monoculture in Northern Thailand. In terms of the social sustainability dimensions of fair trading practices and of decent livelihood, the results suggest that the contract farming system usually employed in the highland maize monoculture in northern Thailand is unsustainable. Finally, we discussed the limitations of the SAFA tool.
Keywords: Forest encroachment; Maize monoculture; Social well-being; Sustainability; Sustainability Assessment of Food and Agriculture System (SAFA)